Una aproximación a la estrategia territorial turística sostenible - López Olivares, Diego (Millars. Espai i Història, 2010)
Nowadays, post-modern society is undergoing many changes in the search for “a state of social welfare”, and to achieve these changes tourism and leisure time activities are vital. In the context of these changes and in contrast to the traditional concept of tourism we have the concept of sustainable tourism which tries to match trends of demand to a higher quality of the tourism spots in which the preservation of the environment and the culture is vital for their competitiveness. Related to these circunstances we now need to think about the situation of the main areas where most tourism is centred, such as the seaside, rural areas, nature environments and urban areas.